Contribution of Planning, IT Based Communication, Implementation and Follow Up Supervision in Elementary Schools - Taufik Nurrochman; Harsono Harsono; Sabar Narimo (Jurnal Penelitian Pendidikan IPA, 2024)
The quality of learning is expected to continue to improve, but supervision management continues to decline. This research aims to identify strategic factors involved in implementing supervision at the elementary school level. Quantitative methods were applied in this research using a census design, where 250 teachers were asked to fill out a questionnaire via the Google Form platform. However, because some teachers were unfamiliar with technology, only 213 teachers responded. The collected data was then analyzed using the Structural Equation Modeling (SEM) method. The findings from this research show that there is a direct influence between supervision planning, IT-based communication and implementation of supervision on supervision follow-up. while supervision planning and IT-based communication influence supervision follow-up through the implementation of supervision